Pancreas of Laying Hens (Gallus gallus domesticus) and Moorhen Birds (Gallinula chloropus) A Comparative Investigation Morphologically, Histo morphologically, and Histologically (Indian Journal of Animal Production and Management, 2025)
Comparatively examining the histological and structural traits of the pancreas  in Gallus gallus domesticus and Gallinula chloropus was the aim of current  study. This study’s main objective was to evaluate these bird species’ value as  reliable suppliers of chicken and eggs. The birds samples are divide for two  groups first group was five laying hens and second group was five moorhen  assigned to anatomical study and histological study. In laying chickens,  the pancreas was distinguished by its white, pinkish coloration while in  Gallinula chloropus was characterized by its white to pinkish coloration.  Histologically speaking, it seems that the Moorhen bird’s connective tissue  capsule was relatively thinner than that of the Laying hens. The connective  tissue capsule, which extends from the septa to the pancreatic parenchyma,  is less common in moorhens than laying hens. Both birds’ exocrine glands  contained serous tubulo-acinar glands. The secretory acini of the Laying  hens possessed pyramid-shaped acinar cells. The presence of oval, elongated  acinar cells was a characteristic of the moorhen bird’s secretory acinar.
Keywords: Gallus gallus, laying hens, Moorhen Birds, pancreas, exocrine glands.